Focus Construction in Àfá - Abdullahi Babátúndé Abdullahi (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
This study examines focus construction process in Àfá; one of the endangered languages of Nigeria. Àfá is spoken in Òkè- Àgbè of Akoko North west local government area in Ondo state. The data for research were gathered from informants who are the native speakers of the language. The sentences with focus paradigm designed by the researcher were dictated to the informants, and their responses were recorded both in short and long hand for purpose of analysis and transcription. The study adopts Government and Binding Theory for its analysis. The study identifies the various constituents that can be focused in the language. It is established that focus construction is derived through Foc that projects into Foc-P and takes IP as its complement. It is discovered that there are two probes in the syntax of Àfá focus: Foc and Emph. This research serves as a part of the documentation of an aspect of the syntax of Àfá.